1979
DOI: 10.1139/v79-223
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of dichlorobis(1-methylcytosine)cadmium(II)

Abstract: Crystals of CdCl2(1-methylcytosine)2 belong to space group Cc, with a = 10.571(7), b = 24.35(2), c = 7.097(3) Å, β = 57.33(4)°, and Z = 4. The structure was refined over 1988 independent reflections to an R factor of 0.026. The structure consists of monomeric molecules in which cadmium has a (4 + 2)-coordination. Four strong bonds, two Cd—Cl (2.497, 2.485 Å) and two Cd—N(3) (2.281, 2.296 Å), define an approximate tetrahedron around the metal. Two carbonyl oxygens take part in weak Cd—O bonding interactions (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
17
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 9 publications
7
17
0
Order By: Relevance
“…The interatomic distances and bond angles are listed in Table 2 (1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The Cd-N(7) distance (2.300(5) A) is similar to those reported for complexes with related ligands (9)(10)(11)(12)(13)(14)(15)(16). N,N-Dimethylformamide is clearly not a constituent of the inner coordination sphere of cadmium, but rather is present in well defined lattice sites as a solvent of crystallization (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The interatomic distances and bond angles are listed in Table 2 (1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The Cd-N(7) distance (2.300(5) A) is similar to those reported for complexes with related ligands (9)(10)(11)(12)(13)(14)(15)(16). N,N-Dimethylformamide is clearly not a constituent of the inner coordination sphere of cadmium, but rather is present in well defined lattice sites as a solvent of crystallization (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Crystal structure analyses on cadmium-nucleobase complexes have shown that the metal ion generally binds to the nitrogen lone pair of N(7) in purines or N(3) in pyrimidines (9)(10)(11)(12)(13)(14)(15)(16). When a carbonyl oxygen is adjacent to these sites, it often participates in "indirect chelation" by forming hydrogen bonds with other ligands in the coordination sphere (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Cd-N bond distances in A and B (2.502 and 2.506 ,/~) fall within the sum of the van der Waals radii for Cd and N (1.50 + 1.5 --3.0 /~) (Pauling, 1967), they considerably exceed the sum of the covalent radii (1.48 + 0.70 --2.18/~) and typically reported values such as 2.292 and 2.289A in CdCI2(NHECaH6NH2) (Andreetti et al, 1971), 2.34/~ in CdCl2(thiocarbohydrazide-N,S) 2 (Bigoli et al, 1971), and 2.281 and 2.296A in CdCIE(1-methylcytosine) (Gagnon et al, 1979). Since the axial Cd-N bond is so unusually long and presumably weak and the long Cd-Clt, is in the other axial position, the best description of the bonding about the Cd atom is probably a (3 + 2) strong-trigonal-weak-axial environment.…”
Section: Resultsmentioning
confidence: 94%
“…2 (3) 105.6 (3) P-C (7) plexes, e.g. Cd-CI = 2.440 and 2.504/k in the monomeric four-coordinate CdCI2[(C6Hs)3P] 2 (Cameron & Forrest, 1971) and 2.485 and 2.497A in the (4 + 2) six-coordinate CdClz(1-methylcytosine) 2 (Gagnon, Beauchamp & Tranqui, 1979). The centrosymmetric dimers A and B exhibit rather unusual asymmetry with both strong (2.484 and 2.520 ,/~) and moderate (2.779 and 2.780 A) bridging Cd-CI bond lengths.…”
Section: Resultsmentioning
confidence: 99%